Função do membro superior em hemiparéticos crônicos: análise através da classificação internacional de funcionalidade, incapacidade e saúde - Iza de Faria (2008)
Relatively few studies have described the function of the upper limb with chronic hemiparetic subjects and the relationships between its specific deficits, function, activities and participation in social activities. The aim of this study was to describe the function of the upper limb with chronic stroke subjects and to investigate the strength of the relationships and the predictive power of specific deficits of the upper limb in preventing the completion of activities and restrictions in social participation. The outcome measures included specific instruments for analyses of the upper limb function in the domains of structure and body functions, activity and participation. The variables related to the structure and body function included control of the voluntary movement stage of motor return of the arm and hand and overall motor return of the upper limb; muscular strength and endurance grip and lateral pinch strength, isometric upper limb strength and resistance; muscle tone - spasticity; manual and digital dexterity; sensory functions and pain - sensation to movement touch and shoulder pain. The activity domain was assessed by the self-reported and observed performance, whereas the participation was evaluated by Stroke Specific Quality of Life - SSQOL-Brazil (total score and score on items related to the upper limb function) and the Canadian Occupational Performance Measure - COPM (performance and satisfaction with their performance in self-reported relevant activities). The final sample was composed of 55 participants with clinical diagnoses of stroke more than six months and ability to execute reaching and grip tasks. Most of the variables related to body structure and function were correlated with the activity measures. In general, the domains related to body structure and function showed moderate correlations with self-reported performance and strong correlations with the observed performance. The participation measures related to the SSQOL-Brazil were moderately correlated with the following body structure and function variables: Grip and pinch strength, and shoulder pain. The satisfaction with the performance on relevant tasks, measured by the COPM, showed to be correlated with digital dexterity. The manual and digital dexterity, together with the stage of motor return of the hand, pinch strength, and shoulder pain explained 91% of the variance of the observed performance in daily activities model. In the other hand, pain and stage of motor return together explained 48% of the variance of the self-reported performance model. When considering social participation, assessed by the SSQOL-Brazil as an outcome variable, the variables related to the structure and body function and activity explained the smallest variance of the analyzed models. Pain demonstrated the highest predictive power for the overall quality of life (16%) and the quality of life items related to the upper limb function (29%). As quality of life is a broad construct which involves different areas of functionality, the inclusion of only upper limb performance measures may explain the low explained observed variance.